From smart to rebel city? Worlding, provincialising and the Barcelona Model. (February 2021) - Charnock, Greig; March, Hug; Ribera-Fumaz, Ramon
This article examines the evolution of the 'Barcelona Model' of urban transformation through the lenses of worlding and provincialising urbanism. We trace this evolution from an especially dogmatic worlding vision of the smart city, under a centre-right city council, to its radical repurposing under the auspices of a municipal government led, after May 2015, by the citizens' platform Barcelona en Comú. We pay particular attention to the new council's objectives to harness digital platform technologies to enhance participative democracy, and its agenda to secure technological sovereignty and digital rights for its citizens. While stressing the progressive intent of these aims, we also acknowledge the challenge of going beyond the repurposing of smart technologies so as to engender new and radical forms of subjectivity among citizens themselves; a necessary basis for any urban revolution.